2002
DOI: 10.1016/s0925-4773(02)00193-4
|View full text |Cite
|
Sign up to set email alerts
|

Inducible RNA interference uncovers the Drosophila protein Bx42 as an essential nuclear cofactor involved in Notch signal transduction

Abstract: We used the UAS/GAL4 two component system to induce mRNA interference (mRNAi) during Drosophila development. In the adult eye the expression from white transgenes or the resident white locus is significantly repressed by the induction of UAS-wRNAi using different GAL4 expressing strains. By induced RNAi we demonstrate that the conserved nuclear protein Bx42 is essential for the development of many tissues. Phenotypically the effects of Bx42 RNAi resemble those obtained for certain classes of Notch mutants, poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…In addition, we found that the Act5C-GAL4 driver on the second chromosome induces a stronger RNAi effect than the Act5C-GAL4 driver on the third chromosome. We also found that a higher culture temperature (29°) can increase the silencing ability of Prat RNAi (data not shown), as found in other reports (Fortier and Belote 2000;Negeri et al 2002), presumably due to the increased GAL4 activity (Duffy 2002). These observations support the idea that the degree of lethality caused by Prat RNAi is dependent on the level of transgene expression, whether it is influenced by position effects, copy number, dosage compensation, or culture temperature.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, we found that the Act5C-GAL4 driver on the second chromosome induces a stronger RNAi effect than the Act5C-GAL4 driver on the third chromosome. We also found that a higher culture temperature (29°) can increase the silencing ability of Prat RNAi (data not shown), as found in other reports (Fortier and Belote 2000;Negeri et al 2002), presumably due to the increased GAL4 activity (Duffy 2002). These observations support the idea that the degree of lethality caused by Prat RNAi is dependent on the level of transgene expression, whether it is influenced by position effects, copy number, dosage compensation, or culture temperature.…”
Section: Resultssupporting
confidence: 91%
“…The absence of the siRNA amplification step in Drosophila means that the silencing ability depends on the relative expression levels of the target gene and the transgene (Negeri et al 2002). This view is supported by our finding that Prat RNAi resulted in higher levels of pupal lethality for males than for females, corresponding to the higher expression of Prat in females .…”
Section: Discussionsupporting
confidence: 63%
“…Knock-down of dTip60 under the control of the daughterless promoter (da-Gal4), which is an early and ubiquitous driver line (Gortchakov et al, 2005), caused pupal lethality at 29°C. This effect was reproduciable with the T80-Gal4 driver line at 29°C (Table 1), which is a late and ubiquitous driver line (Negeri et al, 2002). This indicated that dTip60 is essential, which was consistent with previous work (Zhu et al, 2007).…”
Section: Strong Knock-down Of Dtip60 Led To Lethality Whereas Moderasupporting
confidence: 90%
“…Bx42 is a nuclear transcription factor required for the formation of different tissues during development. Phenotypic analysis of wing imaginal disks suggests that Bx42 is involved in the Notch signaling pathway (39). Treatment of Drosophila cell cultures with Bx42 dsRNA resulted in cell death (10).…”
Section: Resultsmentioning
confidence: 99%